OPTIMIZATION OF FLOATING HORIZONTAL AXIS WIND TURBINE (FHAWT) BLADES FOR AERODYNAMIC PERFORMANCE MEASUREMENT - Sajid Ahammed (International Journal of Innovations in Engineering Research and Technology, 2021)
Wind power is one of the most important sources of renewable energy which extract kinetic energy from the wind. Currently much research has concentrated on improving the aerodynamic performance of wind turbine blade through wind tunnel testing and theoretical studies. However, wind turbine simulation through Computational Fluid Dynamics (CFD) software offers inexpensive solutions to aerodynamic blade analysis problem. The purpose of this paper is to find the effect of angle of attack towards the blade of Floating Horizontal Axis Wind Turbine (FHAWT) and optimize to get the best blade performance in between twisted and untwisted blade which will give maximum lift and drag force ratio. The optimization of the FHAWT blades are carried out by analysing, modelling and simulation by using simplified spreadsheet method, CFD analysis in ANSYS WORKBENCH 2020 R1 software and wind tunnel testing. The blades are evaluated regarding their lift and drag force ratio in different angle of attack and wind speed. The results, obtained from both computer programs, wind tunnel testing and the initial hand calculations, are comparable and satisfying. Finally, the model was implemented to optimize blades performance, especially at low wind velocities, which is crucial to produce power during operating in offshore environment.